2012
DOI: 10.3390/ijerph9020531
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Suicidal Behavior

Abstract: A seasonal suicide peak in spring is highly replicated, but its specific cause is unknown. We reviewed the literature on suicide risk factors which can be associated with seasonal variation of suicide rates, assessing published articles from 1979 to 2011. Such risk factors include environmental determinants, including physical, chemical, and biological factors. We also summarized the influence of potential demographic and clinical characteristics such as age, gender, month of birth, socioeconomic status, metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
2
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 104 publications
(182 reference statements)
12
85
2
12
Order By: Relevance
“…The second summer peak was not observed at that time, coincided with the results of two other studies [44,45]. The discrepancy in peak season is likely due to the biological, cultural, socio-economic and bio-climatic factors which involved in the seasonal pattern of suicidal behavior [46]. As regards the time of the day, the results of the present study indicate that suicide attempts occurred most frequently at night.…”
Section: Discussionsupporting
confidence: 87%
“…The second summer peak was not observed at that time, coincided with the results of two other studies [44,45]. The discrepancy in peak season is likely due to the biological, cultural, socio-economic and bio-climatic factors which involved in the seasonal pattern of suicidal behavior [46]. As regards the time of the day, the results of the present study indicate that suicide attempts occurred most frequently at night.…”
Section: Discussionsupporting
confidence: 87%
“…Although here reduced left STG grey matter volume was observed for spring/summer births in a healthy adult population, based on the observation that both SOB and schizophrenia predict left STG volume, one might speculate this region mediates SOB effects on schizophrenia in a male clinical population. Higher suicide rates in spring/summer vs. fall/winter births have also been consistently observed (Salib and Cortina-Borja, 2006; Woo et al, 2012), while reduced STG volume has been previously observed in suicidal depression vs. non-suicidal depression (Hwang et al, 2010), and in schizophrenic subjects who had attempted suicide vs. not (Aguilar et al, 2008). I speculate that neuroimaging, and in particular STG grey matter volume, could be a valuable intermediate-phenotype (Meyer-Lindenberg and Weinberger, 2006) in bridging the gap between SOB and risk for schizophrenia and suicidality.…”
Section: Discussionmentioning
confidence: 80%
“…Previous research suggests statistical associations between season of birth (SOB) with prevalence of neurobehavioral disorders such as schizophrenia (Davies et al, 2003; Hori et al, 2012a; Bersani et al, 2006; Cohen and Najolia, 2011; Torrey et al, 1997), bipolar disorder (Torrey et al, 1997) and panic disorder (Castrogiovanni et al, 1999), and traits such as lifespan (Doblhammer and Vaupel, 2001), novelty and sensation seeking (Eisenberg et al, 2007; Roussos et al, 2010; Chotai et al, 2009a) and suicidality(Woo et al, 2012; Salib and Cortina-Borja, 2006). Proposed explanations for these associations include variations in infectious disease exposure, nutrition, temperature, maternal hormones, maternal egg quality, birth complications and photoperiod (Jongbloet et al, 2005; Doblhammer and Vaupel, 2001; Schwartz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, suicide rates by season have been reported to peak in the spring in several countries, regardless of geographic location. This seasonal association seems to be stronger for suicide by violent methods and greater in rural areas (for review see (32)). This phenomenon might be related to intensity of seasonal activities such as agricultural work in the rural areas, or ambient pollen concentration (33).…”
Section: Demographic Risk Factorsmentioning
confidence: 99%